NUMERICAL CALCULATION OF PHOSPHATE TRANSPORT IN BENOA BAY, BALI - I Gede Hendrawan; I komang Ardana (International Journal of Remote Sensing and Earth Sciences (IJReSES), 2009)
A computational model to study the phosphate transport in the coastal environment was presented. It calculation involves the external sources of photosphate matter from the river discharge. The phosphjate distribution within the bay forced by tidal current, was calculated by Pricenton Ocean Model (POM) 2-dimension (barotropic mode). The tidal current obtained from simulation, shown a reasonably good agreement with in-situ tidal level data at Benoa tidal gauge station. The phosphate transport is generated by two-river discharge within the bay and three sources respected by wastewater treatment in Nusa Dua Bali, vessel parking area and waste garbage dump in suwung, respectively. The result confirm that a good agreement with the experiment data carried out within the bay. Keywords : phosphate transport, Princeton Ocean Model (POM)